Volatile organic compounds present in the aroma of 17 exotic fruits in Colombia: review - Taborda-Ocampo, Gonzalo; Aguirre-López, Daniela Andrea; López-Calvo, Angela María; López-Calvo, Sandra Milena (Revista Colombiana de Investigaciones Agroindustriales, 2023)
Aroma is the sensation obtained with the activation of olfactory receptors in the human and animal nose, in the presence of Volatile Organic Compounds (VOCs) that are released by organisms as a product of biogenic processes. Fruits often release volatile or semivolatile organic compounds that include different functional groups and heteroatoms such as sulfur and nitrogen, providing particular and differentiating olfactory notes among the different fruits. This fact allows them to carry out chemical communication processes or chemical ecology and confers them organoleptic characteristics useful to establish quality and consumer acceptance parameters. The most common analytical methodology for sampling the volatile environment of fruits is Solid Phase Microextraction (SPME) coupled with Gas Chromatography Mass Spectrometry (GC/MS) to separate and identify compounds. This review makes an inventory of the most abundant volatile organic compounds present in fruits catalogued as exotic in the ripening stage at the point of consumption, to establish differences and similarities in order to consider potential biomarkers of quality. It is also intended to visualize how VOC analysis methods have evolved over the last 20 years. The fruits catalogued in this study as exotic could be native to Colombia or with a high acceptance and consumption in this country, thus selecting: avocado, arazá, carambolo, custard apple, soursop, sour guava, sweet guava, apple guava, gulupa, lulo, mango, passion fruit, melon, papaya, tree tomato, uchuva and sapote. We employed different search methods on exotic fruits in bibliometric networks, using the following descriptors: volatile compounds, volatile, aroma, MEFS and GC/MS (volatile compounds, volatile, aroma, SPME and GC/MS). The results of the various studies analyzed recorded 194 volatile aroma compounds as follows: aldehydes (24,2 %), alcohols (16,5 %), esters (34,0 %) and others -terpenes, ketones, furans, lactones and sulfur compounds- (25,3 %), with their corresponding aroma descriptors for each compound. Since each compound can be repeated in several fruits, the final list presented 39 different types of compounds, to which a multiple correspondence analysis (MCA) was performed, showing a percentage of variability higher than 80 %; with distinctive characteristics that relate to pleasant and unpleasant aromas (off-flavor). The different studies of the volatile fractions of exotic fruits such as carambola, gulupa, lulo, mango, papaya and cape gooseberry determined representative molecules by MCA such as: 1-octen-3-one, 1-hexanol, 1-butanol, linalool, dimethyl disulfide, methional, 3-sulfanyl-hexyl acetate, among others. It was also found that the main aroma descriptors of exotic fruits in Colombia are: fruity, green, mint, sweet, floral and unpleasant aromas such as sulfur, sweaty, greasy, moldy, cooked potato, rancid, onion or mushroom aroma. Finally, this study provides a tool containing the VOCs and aroma descriptors of the exotic fruits included in this study.